The Influence of The influence of servant leadership and innovation on successful women entrepreneurs mediated by self-efficacy - Dewi Nilam Gandasari; Retno Purwani Setyaningrum (Institute of Computer Science (IOCS), 2024)
The aim of this research is to determine the influence of servant leadership and innovation on successful female entrepreneurs mediated by self-efficacy at Perusahaan Dagang (Trading Company) Dua Bintang. The method used in this research is quantitative, the data sources used are primary data, both from questionnaire results and survey data or journals. The sampling technique uses a saturated sample formula and sampling in this research was carried out by distributing questionnaires with a sample size of 69 respondents. This research used software in the form of computer software, namely the SmartPLS VERSION 3.0 program. The results of this research show that (1) the servant leadership variable does not have a significant influence on successful female entrepreneurs. (2) the innovation variable has a significant influence on successful female entrepreneurs. (3) the self-efficacy variable has a significant influence on successful female entrepreneurs. (4) the servant leadership variable has no significant influence on self-efficacy. (5) the innovation variable has a significant influence on self-efficacy. (6) the servant leadership variable which is mediated by self-efficacy does not have a significant influence on successful female entrepreneurs. (7) the innovation variable mediated by self-efficacy has a significant influence on successful female entrepreneurs